Mechanics based approach for ductility of reinforced concrete beams under cyclic loading / Ahmad Azim Shukri - Ahmad Azim , Shukri (2015)
The ductility of reinforced concrete refers to the ability to absorb energy such as that from seismic loading and normal traffic loads. It is an important parameter in reinforced concrete design process, particularly in situations where major cyclic loads are a concern. However, the process of quantifying ductility in reinforced concrete structures is made complex by the interface displacements that dominates the behaviour of reinforced concrete members when cracks appear. Current methods used to quantify ductility are strain-based, therefore they cannot be used to directly simulate interface displacement. Indirect simulation is possible using empirically determined values, but being empirically derived means it cannot be applied outside the testing regime from which it is derived. In recent years a mechanics-based moment-rotation approach was developed to overcome this problem. The approach is primarily displacement-based, which allows it to simulate the interface displacement mechanisms and thus remove the dependency on empirical values. In this research, the mechanics based approach is extended to allow for cyclic loading and also include the use of size-dependent stress-strain relationship for concrete for better simulation of concrete softening. From comparisons with experimental results, it was found that the method was able to simulate the moment-rotation curves of cyclically loaded beam with acceptable accuracy. The maximum moments were simulated with an accuracy between -7.23% and 1.51% while the minimum moments were simulated with an accuracy between -16.55% and -5.83%. From this, it can be seen that the moment-rotation approach give conservative estimations for the strength of RC beams.